Targeting NK-1R attenuates renal fibrosis via modulating inflammatory responses and cell fate in chronic kidney disease - Zhu, Enyi; Liu, Yang; Zhong, Ming; Liu, Yu; Jiang, Xi; Shu, Xiaorong; Li, Na; Guan, Hui; Xia, Yin; Li, Jinhong; Lan, Hui-yao; Zheng, Zhihua (Frontiers in Immunology, 2023)
Background: Renal fibrosis is the final common pathway of chronic kidney disease (CKD), which is clinically irreversible and without effective therapy. Renal tubules are vulnerable to various insults, and tubular injury is involving in the initiation and evolution of renal inflammation and fibrosis. Neurokinin-1 receptor (NK-1R) functions by interacting with proinflammatory neuropeptide substance P (SP), exerting crucial roles in various neurological and non-neurological diseases. However, its roles in renal inflammation and fibrosis are still unknown. Methods: We collected renal biopsy specimens and serum samples of individuals with or without CKD. Additionally, knockout mice lacking NK-1R expression, SP addition and NK-1R pharmacological antagonist treatment in the unilateral ureteral obstruction (UUO) model, and NK-1R-overexpressed HK-2 cells were employed. Results: Renal SP/NK-1R and serum SP were increased in patients with CKD and mice experiencing UUO and correlated with renal fibrosis and function. SP addition enhanced UUO-induced progressive inflammatory responses and renal fibrosis, whereas genetically or pharmacologically targeting NK-1R attenuated these effects. Mechanistically, TFAP4 promoted NK-1R transcription by binding its promoter, which was abolished by mutation of the binding site between TFAP4 and NK-1R promoter. Furthermore, SP acted through the NK-1R to activate the JNK/p38 pathways to modulate cell fact of tubular epithelial cells including growth arrest, apoptosis, and expression of profibrogenic genes. Conclusion: Our data reveals that SP/NK-1R signaling promotes renal inflammatory responses and fibrosis, suggesting NK-1R could be a potential therapeutic target for the patients with CKD.